EFEITO DA CONTAMINAÇÃO CRÔNICA POR NEONICOTINOIDE NO PERFIL QUÍMICO CUTICULAR DE UMA VESPA SOCIAL - CHIROSA, Lucas Santos,; BATISTA, Nathan Rodrigues,; CARDOSO, Cláudia Andréa Lima,; LIMA, Jean Carlos dos Santos,; OLIVEIRA, Vinicius Edson Soares de,; ANTONIALLI-JUNIOR, William Fernando, (ANAIS DO ENIC, 2024)
-